Visitor arrivals forecasts amid COVID-19: A perspective from the Europe team. (May 2021) - Liu, Anyu; Vici, Laura; Ramos, Vicente; Giannoni, Sauveur; Blake, Adam
Abstract: In a context in which the tourism industry is jeopardised by the COVID-19 pandemic, and potentially by other pandemics in the future, the capacity to produce accurate forecasts is crucial to stakeholders and policy-makers. This paper attempts to forecast the recovery of tourism demand for 2021 in 20 destinations worldwide. An original scenario-based judgemental forecast based on the definition of a Covid-19 Risk Exposure index is proposed to overcome the limitations of traditional forecasting methods. Three scenarios are proposed, and ex ante forecasts are generated for each destination using a baseline forecast, the developed index and a judgemental approach. The limitations and potential developments of this new forecasting model are then discussed. Highlights: A new method is developed to provide forecasts under extreme uncertainty. Uncertainly is addressed by applying judgemental adjustments to scenarios. A two steps method combines forecasting, judgemental adjustment and scenarios. A COVID-19 risk exposure index objectively ranks different destinations. The twenty destinations studied will have different recovery patterns.